2001
DOI: 10.1159/000058061
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival in Invasive Squamous Cell Vulvar Carcinoma: A Univariate Analysis

Abstract: The charts of 50 women with invasive squamous cell vulvar carcinoma were reviewed retrospectively, and pathologic, medical and life style factors were analyzed for their possible influence on survival using the Cox regression univariate model. The median age of the cohort was 73.5 years. The patient distribution according to stage was as follows: stage I: 17; stage II: 16; stage III: 12, and stage IVa: 5 patients. The median follow-up was 61 months. The univariate analysis revealed that the overall survival wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This resulted in the exclusion of 12 articles from our systematic review. [12][13][14][15][16][17][18][19][20][21][22][23] If several estimates were reported in the same article, we chose the most fully adjusted estimate (ie, multivariate regression was selected over univariate regression, which was selected over unadjusted Kaplan-Meier analysis). If an article gave site-specific as well as overall estimates, the overall estimate was used in the primary metaanalysis and site-specific estimates were used in meta-analyses by cancer site.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…This resulted in the exclusion of 12 articles from our systematic review. [12][13][14][15][16][17][18][19][20][21][22][23] If several estimates were reported in the same article, we chose the most fully adjusted estimate (ie, multivariate regression was selected over univariate regression, which was selected over unadjusted Kaplan-Meier analysis). If an article gave site-specific as well as overall estimates, the overall estimate was used in the primary metaanalysis and site-specific estimates were used in meta-analyses by cancer site.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…In a study by Kouvaris et al, on univariate analysis, the authors identified possible prognostic factors for vulvar cancer [5]. Overall survival was impacted by advanced stage, ulceration, tumor size, obesity, smoking, diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%